IMPROVING GROWTH AND PRODUCTIVITY OF INDUSTRIAL POTATOES THROUGH BIOFERTILIZATION, PHOSPHATE FERTILIZATION, AND SPRAYING WITH BRASSINOLIDE - AL Shammery, Mohammed; Abdulrasool , Eiman (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The experiment was carried out in southwest Baghdad during fall season 2021 and spring season 2022 that aimed to study the effect of biological inoculation, phosphate fertilization and spraying with Brasinolide on the growth and production of industrial potato of the Arsenal cultivar , the experiment carried out as a three-factors experiment (4 × 3 × 3) in (RCBD), bio-fertilizers distributed into main plot and interaction between phosphorus levels and Brassinolide growth regulator within sub plot using three replicates Bio-fertilizers included Aspergillus niger fungus alone and Bacillus Megaterium bacteria alone and the combination between them. Phosphorus treatments included three levels (0.100, 200) kg p2o5 ha-1 and Brassinolide spraying of three levels of (0, 0.1, 0.2) mg L-1. The results showed the triple combination bio-fertilizer together with the addition of phosphorus at 100 kg p2o5 ha-1 and spraying with Brassinolide, 0.1 mg L-1 produced significant highest plant's height (78.78 and 102.830) cm plant-1 and in the number of main stems (3.333 and 2.250) stem plant-1 for both seasons  respectively. The highest number of leaves was when the two fertilized were added together with phosphorus fertilization at the level of 200 kg p2o5 ha-1 with spraying at a concentration of 0.1 mg L-1 of Brassinolide (105.333 and 194.111) leaf plant-1 for the two seasons  respectively The same combination was characterized by an average tuber weight of 105.185 g tuber-1 in the fall season and this was reflected in the superiority of productivity (35.254 and 36.923) ton ha-1 for the two seasons  respectively, The same combination with a concentration 0.2 mg L-1 from Brassinolide also gave the lowest value of SOD enzyme in the leaves for both seasons (121.667 and 126.000) units of g-1 wet weight.